Inter-organisational relationships between governmental stakeholders in South African elite sport: resource dependency and inter- organisational theoretical perspectives - Jacobs, S.; De Bosscher, V.; Venter, R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction: Stakeholder relationships within high-performance sport are critically important for the success and growth of nations elite sporting systems. The characterisation of the varying type of inter-organisational relationships can directly influence the implementation of the sport policies within practise. Herewith, it is critically important to understand the dynamics these relationships present. If inter-organisational relationships between stakeholders in elite sport are aligned more strategically by nations, then stronger elite sporting systems will be created. The aim of the study was to evaluate the inter-organisational relationships between governmental stakeholders in order to identify the influences it has on the effectiveness of elite sport policies in South Africa (SA). The study contributed to academic scholarship by juxtaposing two theoretical frameworks, namely, the resource dependency (RDT) and inter-organisational (IOR) theoretical perspectives. The case study evaluated the vertical IOR`s between national and provincial stakeholders in one province in SA, namely the Western Cape. Methods: The IOR partnership was examined with the use of an exploratory qualitative method by means of 10 face-to-face, semi structured interviews on the elements identified in the theoretical perspectives. A purposive sampling method was used including only key informants namely; the national and provincial stakeholders in the elite sport portfolio`s, respectively. Data were analysed by means of thematic analysis in order to apply inductive and deductive reasoning in Nvivo (v.12) software. Results and discussion: The theoretical contribution of using both the RDT and the IOR theories in this study, jointly assisted in the knowledge pertaining to why governmental IOR partnerships are formed, in what way they are managed, what the outcomes are, and lastly, how financial resources played a role in the dynamics of these relationships. The major findings illustrated that: (1) there is a perceived lack of clarity relating to the roles and responsibilities of governmental sport stakeholders, (2) too many entities are involved in sport which led to power struggles and non-cooperation, and (3) a lack of funding introduced issues of power within IOR`s. The current results of this study have confirmed what has been found in the literature which relates to the challenging and often overwhelming influence of IOR management (Alexander et al., 2008). The findings of this study add`s to the field of sport management research by illustrating the issues and concerns which obstructed the implementation of elite sport policy in this case study. Similarly, it identified the factors which facilitated the formation, management and outcomes of IOR`s between governmental stakeholders. Jones et al. (2017) argued that a lack of collaboration within IOR`s may impact upon sport entities ability to deliver consistent services.